2019
DOI: 10.3389/fnhum.2019.00057
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Psychophysiological Measures to Assess Cognitive States in Real-World Driving

Abstract: As driving functions become increasingly automated, motorists run the risk of becoming cognitively removed from the driving process. Psychophysiological measures may provide added value not captured through behavioral or self-report measures alone. This paper provides a selective review of the psychophysiological measures that can be utilized to assess cognitive states in real-world driving environments. First, the importance of psychophysiological measures within the context of traffic safety is discussed. Ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
192
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 241 publications
(196 citation statements)
references
References 257 publications
(510 reference statements)
2
192
1
1
Order By: Relevance
“…Overall, these results strengthen previous findings on the positive correlation between the operator's mental workload and θ-activity [2,51,72]. In particular, θ-activity in frontal areas has been associated with brain engagement in cognitive processes such as judgment, problem solving, working memory, decision making, and mathematical problem solving [73]. Here, we found that an increase in the θ-activity occurred predominantly in the right frontal electrodes (i.e., frontal θ-asymmetry).…”
Section: Terrain Complexity Increases Overall θ-Activitysupporting
confidence: 88%
“…Overall, these results strengthen previous findings on the positive correlation between the operator's mental workload and θ-activity [2,51,72]. In particular, θ-activity in frontal areas has been associated with brain engagement in cognitive processes such as judgment, problem solving, working memory, decision making, and mathematical problem solving [73]. Here, we found that an increase in the θ-activity occurred predominantly in the right frontal electrodes (i.e., frontal θ-asymmetry).…”
Section: Terrain Complexity Increases Overall θ-Activitysupporting
confidence: 88%
“…Thermal IR imaging was demonstrated to be a valid technique for assessing variation in cognitive load [52,107,108]. Most of all, it could enable sensing the real-time state of motorists non-invasively i.e., without disrupting driving-related tasks and, unlike RGB cameras, independently from external light conditions [109]. Studies of thermal IR imaging in driving contexts stated that a rise in mental workload leads to an increase in the difference between nose and forehead temperature [108,110].…”
Section: Thermal Ir Imaging-based Affective Computing In Intelligentmentioning
confidence: 99%
“…Previous studies have used physiological measures such as pupil size (Yoss, et al, 1970), body temperature (Molina et al, 2019), skin conductance, blood pressure, etc. (Lohani et al, 2019) to indicate the level of human arousal or alertness, but these lack the fine-grained information necessary to distinguish transient dips from problematic levels of inattention in which task-related information is lost. In particular, we lack detail on how information processing changes in the brain during vigilance decrements.…”
Section: Introductionmentioning
confidence: 99%